MORAL AGENCY ACROSS TRADITIONS: KANT AND AL ZAMAKHSYARI ON FREE WILL AND HUMAN MORALITY FOR SUSTAINABLE FUTURES - Fajar, Ahmad (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This article examines free will and moral agency through a cross-tradition dialogue between Immanuel Kant’s deontological ethics and Muʿtazilite rational theology as articulated by al-Zamakhsharī. Using library research and a comparative-philosophical analysis, it maps how both frameworks relate free will, morality, and human accountability before the moral law and divine justice. The core finding is a functional isomorphism between Kant’s triad—autonomy (rational free will as the condition of moral action), immortality (the soul’s eternity as the horizon of the highest good), and God (the guarantor of the moral order)—and al-Zamakhsharī’s Muʿtazilite triad: luthf (divine enabling toward moral choice), al-Waʿd wa al-Waʿīd (promise-and-threat as a guarantee of justice), and Allah as the source of moral truth and justice. Despite divergent metaphysical commitments, both converge in portraying the human being as a free yet accountable agent. This synthesis proposes a cross-tradition normative ground for future-oriented moral agency—characterized by reason-responsiveness, intergenerational accountability, and a commitment to expanding the horizon of future morality.